Pembuatan e-modul berorientasi higher order thinking skills(HOTS) untuk pembelajaran fisika pada materi kalor dan teori kinetik gas di kelas XI SMA/MA - Yunita Syafitri; Festiyed - Festiyed; Letmi Dwiridal; Renol Afrizon (Universitas Negeri Padang, 2019)
The expected skills in the 2013 curriculum are the ability to master technology, think critically, and have good problem solving. This certainly can be achieved by the teacher making teaching materials that are connected to ICT which contain questions with HOTS level. However, the reality that occurs in the field is that the teaching materials used by teachers are still limited to printed teaching materials that do not contain HOTS questions and lack of ICT use. Therefore, this study aims to produce teaching materials in the form of e-modules which are oriented to HOTS questions and to determine the level of validity of the e-modules. This type of research is a mixed method research or combination research. This study uses a validity test instrument that contains aspects of material substance, learning design, e-module display, software utilization, and high-level thinking (HOTS). The data obtained is then analyzed to determine the validity criteria of the e-module. Based on the research that has been done, it is concluded that the resulting e-module belongs to the very valid category with a value of 82 (%) for the first validity test and 84 (%) with a very valid category for the second validation. Based on the results of the validity test, the HOTS-oriented e-module for learning physics in heat material and kinetic theory of gas in class XI SMA / MA is feasible to be used in the learning process.